2014
DOI: 10.1111/1469-0691.12724
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factor assessment of Tropheryma whipplei in a rural community in Gabon: a community-based cross-sectional study

Abstract: Tropheryma whipplei is the causative agent of Whipple's disease and has been detected in stools of asymptomatic carriers. Colonization has been associated with precarious hygienic conditions. There is a lack of knowledge about the epidemiology and transmission characteristics on a population level, so the aim of this study was to determine the overall and age-specific prevalence of T. whipplei and to identify risk factors for colonization. This molecular epidemiological survey was designed as a cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 23 publications
2
26
3
Order By: Relevance
“…In rural Senegal, the prevalence in healthy individuals reaches 31% . Colonization rates reach up to 40% for children in Gabon and of up to 63% within a sub‐group of children in South‐East Asian Laos . While children <4 years of age were more frequently colonized in Africa , such colonization was preferentially observed in older children in Laos .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rural Senegal, the prevalence in healthy individuals reaches 31% . Colonization rates reach up to 40% for children in Gabon and of up to 63% within a sub‐group of children in South‐East Asian Laos . While children <4 years of age were more frequently colonized in Africa , such colonization was preferentially observed in older children in Laos .…”
Section: Introductionmentioning
confidence: 99%
“…Precarious hygiene conditions have been presumed to be responsible for high colonization rates in resource‐limited tropical countries , with transmission via the fecal‐oral route . Transmissions to European travelers returning from the tropics have been documented and a potential association of T. whipplei detection with tropical sprue has been suspected .…”
Section: Introductionmentioning
confidence: 99%
“…However, T. whipplei is in fact a common bacterium associated with various conditions, such as acute infections (pneumonia and gastroenteritis) and chronic infections (classic Whipple disease and other infections without digestive involvement, including endocarditis and encephalitis) (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). T. whipplei can also be carried in human feces and, less commonly, in the saliva (20)(21)(22)(23); carriage prevalence varies by the age and exposure of the population and by geographic area (21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…A recent study conducted in Gabon, but in an area other than those studied here, reported its high prevalence in stool specimens, and revealed that young age, male sex, and the number of people sharing a bed were factors associated with an increased risk for carriage of T. whipplei. 35 The studies, which are summarized in Table 4, show that the prevalence of bacteremias varies by area and country. Furthermore, the inclusion of rural populations, which are usually more exposed to microorganisms than those in urban areas, is one of the causes for the increased rate of bacteremias in some studies.…”
Section: Discussionmentioning
confidence: 99%